Application of the Javelin Experiment Board Method to Validate Business Ideas in Startup Companies in Tasikmalaya City - Yusuf, Ismail; Kanita, Ghia Ghaida (Universitas Pendidikan Indonesia, 2022)
The purpose of this research is to find out how the influence and application of javelin board in validating startup business ideas. Many startup companies find it difficult to survive in the midle of competition. One of the reasons is that the ideas offered by the company are not useful in the community. One way to validate ideas of products or services offered is to use the javelin experiment board method. This study uses a quantitative descriptive method, with the number of samples in this study as many as 84 respondents. The test results show that 1) Startup companies in Tasikmalaya City have experienced many failures because the products launched have not been needed by consumers in Tasikmalaya City. 2) The use of the Javelin Experiment Board method to validate the idea of a startup company requires considerable effort and time to get the results of validation data for prospective startup company consumers in the City of Tasikmalaya. 3) The Javelin Experiment Board method helps startup business actors validate ideas to minimize failure when companies launch products to the market.